Investigating the Students' Ability in Creating Flash Fiction in Storybird Aplication - Lestari Setyowati; Dina Dwi Feriyanti; Barotun Mabaroh (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2020)
Storybird is an online social application for storytelling that offers a lot of benefits both for readers and student-writers. Students can act like authors who compose fictional stories and illustrate them with artful images. This study is intended to describe the foreign language (EFL) students’ ability in writing flash fiction by using Storybird. The research used content analysis design. The subjects of this study were 32 students of English education study program who joined creative writing course in University of PGRI Wiranegara. The instruments used were documentation and human instrument. The data collection took two months, from June to July 2020.The researchers analyzed 64 flash fictions written by the students in the Storybird application. The result shows that the students’ ability to create flash fiction is very good. The result also shows that 69% of the students is able to write the flash fiction in a complete generic structure. Almost half of them (45%) prefered ‘love’ theme in writing their fiction. The most preferable way to start the story is by introducing the conflict in the opening, and the most preferable type of conflict is the man vs. man type (48%). The result also reveals that the majority of the students use close resolution to end their story (87.5%), while the rest of them favor open resolution with a probability for a sequel to write.